2014
DOI: 10.1371/journal.pgen.1004396
|View full text |Cite
|
Sign up to set email alerts
|

Early Embryogenesis-Specific Expression of the Rice Transposon Ping Enhances Amplification of the MITE mPing

Abstract: Miniature inverted-repeat transposable elements (MITEs) are numerically predominant transposable elements in the rice genome, and their activities have influenced the evolution of genes. Very little is known about how MITEs can rapidly amplify to thousands in the genome. The rice MITE mPing is quiescent in most cultivars under natural growth conditions, although it is activated by various stresses, such as tissue culture, gamma-ray irradiation, and high hydrostatic pressure. Exceptionally in the temperate japo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…With regards to mPing , upregulation of Ping in the ‘3 days after pollination (DAP)’ embryo is proposed to be responsible for the transposition of mPing in EG4 (Teramoto et al ., ). Whether Ping in oscmt3a is also upregulated in the 3 DAP embryo and thus contributes to the mobilization of mPing in oscmt3a would be a future topic of investigation.…”
Section: Discussionmentioning
confidence: 97%
“…With regards to mPing , upregulation of Ping in the ‘3 days after pollination (DAP)’ embryo is proposed to be responsible for the transposition of mPing in EG4 (Teramoto et al ., ). Whether Ping in oscmt3a is also upregulated in the 3 DAP embryo and thus contributes to the mobilization of mPing in oscmt3a would be a future topic of investigation.…”
Section: Discussionmentioning
confidence: 97%
“…We can confidently rule out (i) as a casual factor based on the following evidences: (a) in our previous efforts to induce TE activity by various means (e.g., Lin et al 2006;Yang et al 2012), we did not observe activity of any of the TEs studied here in the rice cultivar. In fact, as documented by other studies (Naito et al 2009;Teramoto et al 2014), rice cultivars with intrinsic TE mobility under normal growing conditions are extremely rare and so far only one (Gimbozu) was identified. (b) As detailed in the "Materials and Methods" section, Jijing88 was a pure-line rice cultivar and plants used for the pollination experiment had been purposely selfed for several additional generations.…”
Section: Pollination By Zizania As the Underlying Cause For The Mobilmentioning
confidence: 78%
“…However, the mechanism by which Ping16A_Stow may initiate the burst is unknown and warrants further investigation. Prior studies indicated that increased Ping transcripts were correlated with more mPing transpositions in strains undergoing mPing bursts 4,22 . Our unpublished data suggests that Ping16A_Stow does not produce more transcripts compared to other Ping elements, suggesting that mechanisms other than an increased transcript level from this locus may be responsible.…”
Section: Resultsmentioning
confidence: 99%
“…The vast majority of strains with Ping16A have only one Ping (105/154 strains) and a moderate number of mPing elements (mean = 28). One of these strains is the reference strain Nipponbare where the inability to detect transposition of Ping or mPing was initially attributed to Ping silencing 22 . In fact, Ping is not silenced in Nipponbare nor in any other strain analyzed to date 4 .…”
Section: Resultsmentioning
confidence: 99%